IMPLEMENTATION OF THE PAI LEARNING MODEL TO IMPROVE RELIGIOUS MODERATION AMONG IPB UNIVERSITY STUDENTS - Ginanjar, Muhammad Hidayat; Rahman, Rahman; Badrudin, Arief Rahman; Hidayat, Rifqi (Sekolah Tinggi Agama Islam Al Hidayah, 2024)
This research aims to determine and analyse the implementation of the Islamic Religious Education (PAI) learning model to enhance religious moderation. The research was conducted at IPB University using a qualitative approach. Data collection techniques included observation, interviews, and document studies involving lecturers and students as the research subjects. The findings indicate, among others: (1) the PAI learning model is established before lectures, starting from planning, scheduling, assistant assignments, teaching materials, and conditioning learning facilities; (2) the curriculum used in PAI learning integrates the national MBKM curriculum with IPB University's curriculum, (3) the core material of PAI courses at IPB University consists of Islamic material integrated with various disciplines (science) and technologies that can positively impact openness to perspectives, critical thinking, moderation, implemented in daily morality on campus, (4) Religious moderation among students has been implemented conducive manner. This is influenced by several factors, including guidance, correct understanding of religion, a healthy academic climate, students' maturity in behaviour demonstrating friendship, and the exemplary behaviour of lecturers in interacting with fellow campus citizens by teaching theories and practices of tolerance among religious communities.